2018
DOI: 10.30543/7-2(2018)-17
|View full text |Cite
|
Sign up to set email alerts
|

Audit Fees and Financial Reporting Quality: A Study of Listed Companies in Nigeria

Abstract: This paper examines the relationship between audit fees and financial reporting quality of listed firms in Nigeria. We use 88 listed companies in Nigeria for the period of 2012 to 2016. The data were obtained from the annual reports of the listed firms and Thompson Reuters DataStream. Accruals model was used to represent financial reporting quality. A multiple regression was employed in the estimation model. The study reveals that higher audit fees are associated to lower level of discretionary accruals and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Moreover, higher audit fees can indicate the restatement of financial reports and can also be used to assess the quality of financial reporting of a firm. Therefore, the audit fees ratio index has also been used as a determinant of financial reporting disclosure quality, consistent with Tang (2008), Bala et al (2018) and Shakhatreh et al (2020). Lantto and Shalstrὂm (2009) used key financial indicators as proxy indicators to measure a firm's financial reporting disclosure quality.…”
Section: Ifrs Compliance As a Measure Of Financial Reporting Disclosure Qualitymentioning
confidence: 93%
“…Moreover, higher audit fees can indicate the restatement of financial reports and can also be used to assess the quality of financial reporting of a firm. Therefore, the audit fees ratio index has also been used as a determinant of financial reporting disclosure quality, consistent with Tang (2008), Bala et al (2018) and Shakhatreh et al (2020). Lantto and Shalstrὂm (2009) used key financial indicators as proxy indicators to measure a firm's financial reporting disclosure quality.…”
Section: Ifrs Compliance As a Measure Of Financial Reporting Disclosure Qualitymentioning
confidence: 93%
“…SHPREACT it = β 0 +β 1 AUDCIND it + β 2 AUDEXP it + β 3 AUDITSIZ it + β 4 AUDMET it + β 5 AUDCDIV it + e it (2) where: The main technique used for data analysis is the panel regression model. The Hausman Specification test result is used to select between the fixed and random effect models.…”
Section: Independentmentioning
confidence: 99%
“…The audit committee is one of such mechanisms used to ensure the firm is properly managed" [1]. "In Nigeria, there has been massive fraud and unethical practices within and among a number of firms" [2]. "The Companies and Allied Matters Act (CAMA) 2004 [3] as amended in 2020 which was enacted to ensure that the relationship among the board, shareholders and the management including other stakeholders is balanced for healthy competition, has not lived up to expectation as a result of unethical business practices by managers which has affected the financial performance and share price reaction of many firms in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Martinez and Moraes (2017) using a sample of 300 firms listed on the BM&FBovespa, Brazil for the period 2009 to 2012 showed a negative relationship between the cash flow and earnings management. Using a sample of 88 firms in Nigeria, Bala et al (2018) revealed that higher audit fees are associated with a lower level of discretionary accruals; and, Choi et al (2010) found an asymmetric relationship between unexpected (abnormal) audit fees and abnormal accruals. The results showed that abnormal audit fees are negatively associated with abnormal accruals for observations with positive values; whereas, no significant relationship exists for observations with negative values.…”
Section: Residual Audit Fee and Real Income Smoothingmentioning
confidence: 99%